2020
DOI: 10.1093/mnras/staa3017
|View full text |Cite
|
Sign up to set email alerts
|

Sub-Chandrasekhar-mass detonations are in tension with the observed t0−MNi56 relation of type Ia supernovae

Abstract: Type Ia supernovae (SNe Ia) are likely the thermonuclear explosions of carbon-oxygen (CO) white-dwarf (WD) stars, but their progenitor systems remain elusive. Recent studies have suggested that a propagating detonation within a thin helium shell surrounding a sub-Chandrasekhar mass CO core can subsequently trigger a detonation within the core (the double-detonation model, DDM). The outcome of this explosion is similar to a central ignition of a sub-Chandrasekhar mass CO WD (SCD). While SCD is consistent with s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
30
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 73 publications
6
30
0
Order By: Relevance
“…The converging detonation waves trigger a second detonation at the carbon-oxygen core, hence producing a prompt eruption (Moll et al 2014;Raskin et al 2014;Tanikawa et al 2019;Gronow et al 2020). While some observational results seem to favor the double-degenerate scenario (Woosley & Kasen 2011;Maoz et al 2014;Glasner et al 2018), suggesting that they might constitute the majority population of thermonuclear supernovae (Flörs et al 2019;Cheng et al 2020;Li et al 2021), some recent studies found that they could be in a tight tension with the γ-ray ejected time against nickel-mass relation (Kushnir et al 2020).…”
Section: Appendix a Accuracy Of Linear Interpolationmentioning
confidence: 99%
“…The converging detonation waves trigger a second detonation at the carbon-oxygen core, hence producing a prompt eruption (Moll et al 2014;Raskin et al 2014;Tanikawa et al 2019;Gronow et al 2020). While some observational results seem to favor the double-degenerate scenario (Woosley & Kasen 2011;Maoz et al 2014;Glasner et al 2018), suggesting that they might constitute the majority population of thermonuclear supernovae (Flörs et al 2019;Cheng et al 2020;Li et al 2021), some recent studies found that they could be in a tight tension with the γ-ray ejected time against nickel-mass relation (Kushnir et al 2020).…”
Section: Appendix a Accuracy Of Linear Interpolationmentioning
confidence: 99%
“…Here, 〈Σ〉 Ni56 is the column density of the ejecta Ni 56 and κ eff is the effective opacity ( ≈ 0.025 cm 2 g −1 for 56 Co; Swartz et al 1995;Jeffery 1999;Kushnir et al 2020). In a homologous expansion, 〈Σ〉 Ni56 t 2 is constant.…”
Section: The Fast Radioactive Shell Scenariomentioning
confidence: 99%
“…Once luminosities are corrected, we determine the amount 56 Ni from the relation log 10 (𝑀 Ni ) = −0.4(𝑀 𝐵 + 19.841 ∓ 0.020) (Scalzo et al 2014, eq. 2), and the WD masses from the fitting relation 𝑀 wd = (0.796 ± 0.008) + 0.383𝑀 Ni (Kushnir et al 2020) which assumes pure detonations, in agreement with Steigerwald & Tejeda (2021). Once we have the SN Ia explosion masses, we determine the PBH mass scale according to Steigerwald & Tejeda (2021) assuming the WD mass function of Kilic et al (2020).…”
Section: Discussionmentioning
confidence: 99%